The Implications of Muhkamat and Mutasyabihat in the Interpretation of the Qur'an - ‘Ulyan, Mohammad; Rofiq, Nur; Tamami, Muhammad Zaki (Yayasan Azhar Amanaa Yogyakarta, 2023)
Many people interpret the verses of the Koran just by reading the translation. It is very possible for errors to occur in interpreting the Koran. Muslims who only learn religious knowledge from social media to the phenomenon of the 'impromptu ustadz' who may not really understand Islam in depth. They only have skills in public speaking or the ability to speak in public. Therefore, the understanding of the science of interpretation of the Koran must be studied perfectly. One of the efforts in understanding the interpretation of the Koran is knowing the verses of muhkamat and mutasyabihat. Research conducted by the author uses qualitative methods with a research literature approach. The locus of research in this article focuses on the science of the Koran, especially in relation to muhkamat and mutasyabihat in relation to the interpretation of the Koran. The source of the data in this study comes from the literature relating to muhkamat and mutasyabihat. Data collection techniques in this study using library techniques. The results of this study display data about the meaning of muhkamat and mutasyabihat, the opinion of the clergy and the wisdom of the verses of muhkamat and mutasyabihat. Scholars differ in their interpretation of mutasyabihat verses. The salaf scholars are of the opinion that no one knows about mutasyabih except Allah and humans only believe in it. Whereas khalaf scholars argue that people who in their knowledge know about mutasyabih takwil.